Implementation of Technology-Based Arabic Language Learning Media - Muhammad Safitri; Nurul Wahdah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the application of technology-based Arabic learning media designed to improve the quality and effectiveness of learning in the digital era. Using a literature review approach, this study identifies various platforms, applications, and current technologies that can be used in learning Arabic. The findings show that technology-based learning media, such as mobile applications, e-learning platforms, and AI-based technologies, are able to provide an interactive, flexible, and engaging learning experience. In addition to benefits such as increased learning motivation and easy access to materials, this study also found challenges in its implementation, such as limited technology infrastructure and lack of teacher skills in using technology. This study contributes to the understanding of how to utilize technology to overcome traditional barriers in learning Arabic, while also providing recommendations for further development in this area.